2013
DOI: 10.2340/00015555-1625
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Full Clinical Examination: Assessment of Index Lesions Referred to a Skin Cancer Clinic Without a Total Body Skin Examination Would Miss One in Three Melanomas

Abstract: Traditional clinical teaching emphasises the importance of a full clinical examination. In the clinical assessment of lesions that may be skin cancer, full examination allows detection of incidental lesions, as well as helping in the characterisation of the index lesion. Despite this, a total body skin examination is not always performed. Based on two prospective studies of over 1,800 sequential patients in two UK centres we show that over one third of melanomas detected in secondary care are found as incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 12 publications
(10 reference statements)
5
40
1
2
Order By: Relevance
“…The US Preventive Services Task Force does not currently recommend routine skin cancer screening in the general population by primary care physicians because of insufficient evidence concerning its benefits and harms. 40 However, other studies [41][42][43] suggest skin cancer screening can significantly increase early detection of skin cancer and decrease disease-related mortality. Identifying sexual minority men as a high-risk population for skin cancer may help physicians risk stratify those patients in whom more diligent screening might be more beneficial.…”
mentioning
confidence: 99%
“…The US Preventive Services Task Force does not currently recommend routine skin cancer screening in the general population by primary care physicians because of insufficient evidence concerning its benefits and harms. 40 However, other studies [41][42][43] suggest skin cancer screening can significantly increase early detection of skin cancer and decrease disease-related mortality. Identifying sexual minority men as a high-risk population for skin cancer may help physicians risk stratify those patients in whom more diligent screening might be more beneficial.…”
mentioning
confidence: 99%
“…15 Additionally, it is not possible to perform full-body skin examinations, 56 and some authors have reported that relying on teledermatology to assess pigmented lesions may lead to under-detection of melanoma by general practitioners. 35,57 Therefore, teledermatology will not completely replace FTF consultations. Instead, it can be useful as a triage tool, to qualify which patients really need FTF specialized care and help to define the priority in which this care should be delivered.…”
Section: Challengesmentioning
confidence: 99%
“…12 Aldridge et al discovered 5 incidental melanomas among 336 patients referred from primary care for evaluation of lesions suspicious for skin cancer. 13 Kingsley-Loso et al discovered 87…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] This concern is more related to the perceived inability of primary care providers (PCPs) to direct imaging of suspicious lesions than to the SFT dermatologist's ability to diagnose them. [12][13][14] At least three previous studies have ascertained the frequency of ''incidental'' melanomas in populations of patients referred for FTF dermatology care. An incidental melanoma is defined as a melanoma discovered by a dermatologist during full body skin examination (FBSE), but was not the subject of the referral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation